Development and evaluation of an augmentative and alternative communication training for caregivers of young children in a low-income rural context of South Africa - Tonsing, Kerstin Monika (University of Pretoria, 2023)
Thesis (PhD (Augmentative and Alternative Communication))--University of Pretoria, 2022.